Participatory road infrastructure and Sustainable Development Goals: an andean model for sustainable - Juan Eduardo Suárez Rivadeneira; Freddy A. Manayay; Wilfredo Ruiz Camacho; Ghilmar Brayan Perales Rojas (Clío)
This article analyzes the Participatory Road Development Plan for Cutervo Province (Peru), focusing on how road strategies can promote local economic development, social equity, and environmental sustainability. Using a participatory methodology and tools such as georeferenced road inventory and geographic information systems (GIS), the study identifies priority routes for intervention and proposes strategies that integrate road connectivity improvement with the promotion of local production, sustainable rural tourism, and environmental management practices. The results show that only 6.5% of the routes are paved, limiting access to basic services and markets and affecting the quality of life and economic opportunities of the population. The analysis and discussion of the results reveal the importance of addressing road infrastructure as a key driver of local sustainable development, proposing recommendations for future policies that further integrate the economic, social, and environmental dimensions in road planning.